Prinsip-Prinsip Pengajaran Yesus yang Berorientasi Membangun Pembelajaran yang Efektif dan Tranformatif - Gimson Sitinjak; Yoshua Fordin Hasiolan; Menderita Lilis Purba; Selfius Dur; Lenny Lubis; Yusniarti Situmorang; Wilson Simanjuntak (Pusat riset dan Inovasi Nasional, 2025)
This paper discusses the principles of Jesus’ teachings that are relevant for building effective and transformative learning within the context of contemporary education. Jesus is known as the Great Teacher who taught with authority, closeness, and methods capable of transforming the thinking, attitudes, and behavior of His listeners. Through biblical analysis and pedagogical examination, this study identifies several key principles, including the use of stories and parables to facilitate deep understanding, a dialogical approach that encourages active participation, contextualization of the message according to the listeners’ social background, modeling as a form of learning through example, and an emphasis on character transformation as the ultimate goal of education. The study concludes that the principles of Jesus’ teaching are not only effective in delivering content but also play a significant role in shaping the internal transformation of learners. By adapting these principles, modern educators can build learning processes that are more meaningful, holistic, and transformation-oriented.